The Effect of Financial and Non-Financial Indicators on the Profitability of Islamic Commercial Banks in Indonesia - Mardillasari, Rafika; HS, Sufyati; Muktiyanto, Ali (LPPM Universitas Terbuka, 2021)
This study aims to analyze the influence of financial indicators (CAR, FDR, BOPO, NIM, NPF) and non-financial (number of bank offices, market share, GCG, CSR) on profitability that is proxied by Return on Assets (ROA) of Islamic Banks in 2014 -2018. The data source used is secondary data from 2014-2018. Data analysis techniques used are descriptive analysis, multiple linear regression analysis and the classic assumption test. Findings. The results of the study are that CAR does not have a significant negative effect. FDR does not have a significant negative directional effect. BOPO has a significant negative effect. NIM has a positive positive significant effect. NPF has a significant negative effect. The number of bank offices has no significant positive effect. Market share does not have a significant negative directional effect. GCG does not have a significant negative effect. CSR has a significant negative effect. The adjusted R2 value is 73.21% while the remaining 26.79% is influenced by other variables outside the study so the researcher should further add other variables.